LAGU ANIMASI NUSSA DAN RARA PERSPEKTIF PENDIDIKAN ANAK USIA DINI - Ichromsyah Arrochman; Siti Chotimah (Program Studi Pendidikan Islam Anak Usia Dini, 2022)
The appearance of the animated film Nussa and Rara on Youtube, in the episode of eating don't just eat which was watched by 88 million viewers, both children and adults and had 7.88 million subscriptions. The presence of this song is a highlight for the community. According to researchers, it is in accordance with this study that the education of moral and religious values requires a more modern, rational, comprehensive media, easily captured and lived by students. The problem is what moral and religious values and health are contained in nussa and Rara's animated songs, don't just eat from an early childhood Islamic education perspective. In this case, the researchers chose library research by taking the object of nusa and Rara animated songs episodes of eating don't just eat, through a Pragmatic approach and data collection was carried out through documentation. The results showed: First, moral and religious values: teaching the ethics of decency: a. always prioritize the right part in doing anything, b. start activities with good intentions, c. eat according to the portion in order to achieve blessings, d. the importance of maintaining cleanliness before and after eating, e. when eating and drinking while sitting. Second, for the world of health; a. overeating and irregularly can cause indigestion and give rise to a wide variety of diseases, b. eating with dirty hands can cause diarrhea, c. whereas Eating by hand and licking fingers to clean them is beneficial in helping smooth digestion, d. drinking in a standing position can provoke the occurrence of acid reflux of the stomach. e. not consuming food while it is still hot because it results in an imbalance in metabolism.